Pemahaman Mendasar tentang Konseling Kelompok bagi Praktisi Bimbingan dan Konseling - Pratiwi, Utari; Karneli, Yeni; Netrawati (Siber Nusantara Publisher, 2024)
Group counseling is a service using a group approach that is often used by guidance and counseling practitioners in schools. However, there are still practitioners who are still unsure about understanding the basics of group counseling. So it can reduce the effectiveness of the services provided to clients. The method used in analyzing problems is literature study sourced from books, articles and scientific journals that are relevant to group counseling. The results of the literature study analysis that have been carried out show several basic things that need to be understood by guidance and counseling practitioners in understanding group counseling, namely the meaning, objectives, scope of service materials, function of group leaders, principles and steps for implementing group counseling. Having this understanding makes it easier for practitioners to provide group counseling services professionally.